Rethinking Spirituality through Music Education in Istanbul - Banu Şenay (European Journal of Turkish Studies)
Recently there has been a massive new interest in Turkey in the artistic practice of ney [reed flute]-playing. For some, much of the inspiration driving this interest connects to a search for the “spiritual.” According to a popular discourse, there is no instrument more “natural” and “simple” than the ney. For others, inspired by the poetry of Rumi, the instrument’s sound draws oneself closer to the Divine. While a close connection exists between this “spiritualization” of the ney and contemporary commercial developments in the global and Turkish music industry, the Turkish state too has been active in creating meanings about the “spiritual ney” by incorporating it into its tourism industry and nationalist ideology. By contrast, the critical reflections of the master musicians that my fieldwork study examines suggest a very different conception of spirituality. Here the “spiritual” experience of this musical practice is understood to be grounded not in the sounds of the instrument itself, but in learning the art in a certain way.